A Sustainable Freeze‐Drying Route to Porous Polysaccharides with Tailored Hierarchical Meso‐ and Macroporosity. Issue 8 (26th February 2015) - Borisova, Aleksandra; De Bruyn, Mario; Budarin, Vitaliy L.; Shuttleworth, Peter S.; Dodson, Jennifer R.; Segatto, Mateus L.; Clark, James H.
<x xml:space="preserve">Abstract</x> Bio‐derived polysaccharide aerogels are of interest for a broad range of applications. To date, these aerogels have been obtained through the time‐ and solvent‐intensive procedure of hydrogel fomation, solvent exchange, and scCO2 drying, which offers little control over meso/macropore distribution. A simpler and more versatile route is developed, using freeze drying to produce highly mesoporous polysaccharide aerogels with various degrees of macroporosity. The hierarchical pore distribution is controlled by addition of different quantities of t‐butanol (TBA) to hydrogels before drying. Through a systematic study an interesting relationship between the mesoporosity and t‐butanol/water phase diagram is found, linking mesoporosity maxima with eutectic points for all polysaccharides studied (pectin, starch, and alginic acid). Moreover, direct gelation of polysaccharides in aqueous TBA offers additional time savings and the potential for solvent reuse. This finding is a doorway to more accessible polysaccharide aerogels for research and industrial scale production, due to the widespread accessibility of the freeze drying technology and the simplicity of the method. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>